Mathematical modelling of container loading in port with/without temporary container storage area: An HSE-based approach - Negar Yarmohamadi; Saeed Yaghoubi (Transportation Research Interdisciplinary Perspectives)
Efficient container port operations rely on integrated processes including berth allocation, quay crane assignment, and yard truck planning. A significant challenge within these operations is managing the health, safety, and environmental (HSE) risks associated with workers’ fatigue, particularly during night shifts. Fatigue-related risks can lead to operational inefficiencies, increased accidents, and compromised safety outcomes, highlighting the need to address them within port optimization frameworks. This research presents two mathematical models to enhance container handling: the Temporary Containers Storage Model (TCSM) and the Direct Containers Loading Model (DCLM). In both models, the container yard is partitioned into blocks, with each block assigned to containers from a specific vessel. The berth is divided into positions where ships dock, and cranes are used to load containers onto the vessels. Effective resource management is essential to ensure that all containers are loaded before vessel departure. Analysis using the Lagrangian relaxation method at Shahid Rajaee Port reveals that workers experience 24 % more fatigue under the DCLM compared to the TCSM, despite the DCLM also leading to 22 % higher costs. These findings emphasize the critical importance of incorporating HSE considerations into container port operations, not only to improve safety and worker well-being but also to achieve long-term cost savings and enhanced productivity.